Growing black holes: accretion in a cosmological context: proceedings of the MPA ESO MPE USM Joint Astronomy Conference, held in Garching, Germany, 21 - 25 June 2004 - Merloni, Andrea (Springer, 2005)
Supermassive black holes (SMBH) are among the most spectacular objects in the Universe, and their study sheds light on fundamental physical phenomena occurring in their immediate vicinity, such as accretion of gas and general relativistic effects. However, in recent years, it has been established that SMBH are not just interesting laboratories of strong gravity and high-energy astrophysics, but have direct impact on the evolution of the large scale structure and have an influence on the appearance of our Universe. For this reason, scientists from the extra-galactic astronomy, cosmology and accretion physics communities were brought together to discuss the implications of the connection between the supermassive black hole growth and galaxy formation. The Conference "Growing Black Holes: Accretion in a Cosmological Context'' was held in Garching during June 21-25, 2004 as a part of the joint MPA/MPE/ESO/USM Astronomy conference series. The meeting was attended by about 170 scientists from more than 20 countries all over the world. These proceedings contain the excellent review and invited talks that summarized the state of the art in the research on the respective topic as well as the equally interesting contributed talks and poster papers, many of which presented original ideas or latest observational results. This book is thus a useful research and reference tool for the entire astrophysical community. TOC:First Supermassive Black Holes and Structure Formation.- Observations of Supermassive Black Holes at Higher Redshift.- Observations of Super Massive Black Holes in the Local Universe.- The Case of Sagittarius A*.- Interaction of Supermassive Black Holes with Their Environment.- Physics of Accretion Discs Around Supermassive Black Holes.- Black Hole-Black Hole Mergers and Gravitational Waves.- Jeds, Outflows and QSO Feedback.- The Cosmological Evolution of Active Galactic Nuclei and the X-Ray Background
Literaturangaben
Keywords: Konferenzschrift -- München, 2004 -- Garching; Konferenzschrift -- 2004 -- Garching, München; Kosmologie; Akkretion; Schwarzes Loch